Development of Context-Based English Learning Materials for Automotive Vocational High School Students - Arfiansyah, Aditya; Tyas Alhim Mubarok; Widiarini, Widiarini (Scripta : English Department Journal, 2024)
This study examined the development of context-based English learning materials for Grade 11 automotive students at SMKN 1 Nglegok, addressing the need for vocationally relevant English resources within the Merdeka Curriculum framework. Using a Research and Development approach, the study created five units focused on automotive language needs, such as workshop communication and customer interaction, employing Context-Based Learning (CBL) principles to enhance real-world applicability. Feedback from teachers and students indicated high satisfaction with the materials’ relevance, comprehensive language components, and engaging, interactive elements. Positive responses highlighted the materials' role in improving job readiness, though some feedback suggested the need for refinements, such as adjusting language complexity and incorporating more multimedia support to address diverse proficiency levels. Overall, this research highlights the importance of context-specific English materials in vocational education, providing foundational insights for future enhancements to better equip students with practical language skills for industry applications.